Binder, positive pole piece as well as preparation method and application of positive pole piece

The integrated binder is prepared by covalent bonding of polycarboxylic acid water reducer and MXene material, which solves the problem of high interface impedance in sulfide solid-state batteries, and achieves the improvement of high positive electrode material load and mechanical properties, which significantly improves the Electrochemical properties of batteries.

CN119463744AActive Publication Date: 2025-02-18QINGDAO INST OF BIOENERGY & BIOPROCESS TECH CHINESE ACADEMY OF SCI
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411636933.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-02-18
Estimated Expiration
2044-11-15

AI Technical Summary

Technical Problem

The prior art is difficult to prepare a sulfide solid electrolyte-based positive electrode with high positive electrode material load and excellent mechanical properties, and the high electrode/electrolyte interface impedance limits the commercial application of solid-state batteries.

Method used

The integrated binder is prepared by covalent bonding of polycarboxylic acid water reducer and MXene material to achieve uniform dispersion of MXene material in non-polar solvents and act as a binder for the positive electrode of the sulfide solid electrolyte.

Benefits of technology

It significantly improves the electrochemical performance of sulfide all-solid state batteries, including low interface impedance, high interface stability and high compatibility, and improves the cycle stability and rate performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119463744A_ABST
    Figure CN119463744A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of all-solid-state batteries, and particularly relates to a binder, a positive pole piece and a preparation method and application of the positive pole piece. The invention provides a binder. The binder comprises a polycarboxylic acid water reducing agent and MXene. The integrated binder is prepared by covalent bonding of the polycarboxylate superplasticizer and the MXene material, and uniform dispersion of the MXene material in a non-polar solvent is realized, so that the MXene material can be used as a binder of a sulfide solid electrolyte positive electrode. The binder can improve the stability of the positive electrode on one hand, can reduce the interface impedance of the sulfide solid electrolyte / positive electrode material on the other hand, and finally improves the overall performance of the all-solid-state battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of all-solid-state batteries, and specifically relates to a binder, a positive electrode plate, and a preparation method and application thereof. Background Art

[0002] On the road to achieving carbon neutrality, the rapid development of industries such as new energy vehicles continues to help reduce carbon emissions. However, the current frequent electric vehicle combustion accidents have affected the large-scale popularization of electric vehicles. The main reasons for the frequent safety accidents of electric vehicles include overheating, overcharging, internal short circuit or mechanical abuse of power batteries, and loss of control of battery management systems. For lithium batteries themselves, the use of organic electrolytes with poor safety is the root cause of battery fires. In contrast, solid electrolytes have higher safety. Therefore, as the next generation of energy storage devices, the development of all-solid-state batteries has received great attention from all walks of life. Among them, sulfide electrolytes have high ionic conductivity and high deformability. They can be in close contact with active materials through cold pressing methods to achieve low interface resistance, making them the most promising solid electrolyte materials. However, the serious interfacial side reactions between the electrolyte and the oxide positive electrode restrict the long cycle performance of sulfide electrolyte-based all-solid-state batteries. To date, the preparation of sulfide solid electrolyte-based positive electrodes (binder content <5wt%) with high positive electrode material loading and excellent mechanical properties remains a difficult problem. In addition, high electrode / electrolyte interface impedance is one of the key issues limiting the commercial application of solid-state batteries.

[0003] The high conductivity of MXene two-dimensional materials and their strong attractive interactions with active material particles enable effective encapsulation, thereby providing an electronic conductive path, achieving rapid ion transfer and capacitive contribution to stored charge. Due to the excellent mechanical properties of MXene and the attractive force acting between its oxygen- and hydroxyl-terminated 2D sheets, it is relatively easy to prepare a membrane with high electronic conductivity. Gogotsi et al. used MXene materials to prepare sodium ion battery binders for NaTi2(PO3)4(NTP) positive electrodes. Compared with electrodes prepared from traditional PVDF, the integrated NTP / MXene electrode exhibits excellent electrochemical performance in terms of capacity, rate capability and long-term stability (Nano Energy 79(2021)105433). CN115602850A discloses a surface modification of an active material and uses MXene as a conductive agent to achieve cross-linking bonding between the conductive agent and the active material and the binder, forming a point-line-surface combined three-dimensional network structure Si-APS-M-SA electrode. This three-dimensional network structure greatly improves the overall stability of the electrode, filling the technical gap of improving electrode stability from the perspective of conductive agents; CN113292139A discloses a sub-titanium oxide / MXene / Co3O4 composite electrode and its preparation method, which uses the unique structure of MXene to promote the dispersion of nano-Co3O4, and uses the interpenetration of Co3O4 in MXene to inhibit MXene stacking. Sub-titanium oxide peptides as substrates play a role similar to that of adhesives under high temperature and high pressure. The Co-O-Ti bond generated by sub-titanium oxide peptides, MXene and Co3O4 is used to fix the cobalt element on the sub-oxidized substrate, thereby enhancing the stability of the composite electrode.

[0004] Although MXene materials have been widely used in the battery industry, there are no reports on the use of MXene materials in sulfide solid electrolyte composite electrodes. The reason is that sulfide solid electrolytes are very sensitive to polar solvents such as water and ethanol, and the solubility of MXene materials prepared by conventional methods reported in the literature is often less than 0.5 mg / ml in non-polar solvents, which cannot meet the needs of sulfide solid-state batteries. Summary of the invention

[0005] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, an embodiment of the present invention provides a binder that can achieve uniform dispersion of MXene materials in a non-polar solvent, thereby being able to serve as a binder for a sulfide solid electrolyte positive electrode.

[0006] The binder according to the embodiment of the present invention includes a polycarboxylate water-reducing agent and MXene.

[0007] The advantages and technical effects brought by the binder of the embodiment of the present invention are as follows: 1. In the embodiment of the present invention, an integrated binder is prepared by covalent bonding of a polycarboxylic acid water-reducing agent and a MXene material, so that the MXene material can be evenly dispersed in a non-polar solvent, thereby serving as a binder for solid-state batteries; 2. In the embodiment of the present invention, a sulfide solid electrolyte-based positive electrode prepared with the binder has low interfacial impedance, high interfacial stability and high compatibility with high-voltage positive electrode active materials, which can significantly improve the electrochemical performance of sulfide all-solid-state batteries.

[0008] In some embodiments, the mass proportion of the polycarboxylate water-reducing agent is 10-40%, and the mass proportion of the MXene is 60-90%.

[0009] In some embodiments, the structure of the polycarboxylate water reducer is as shown in formula (1):

[0010]

[0011] In formula (1), R0 is selected from a carboxylic acid group or a sulfonic acid group; R1, R2, R3, R4, R5, and R6 are independently selected from hydrogen, halogen, carbamoyl, alkoxy, alkyl, alkylamino, alkylthio, alkoxysilyl, alkanoyl, sulfonyl, aryl, or heteroaryl; x is 0 to 1000, y is 100 to 1000, and z is 0 to 100.

[0012] In some embodiments, the chemical formula of the MXene is M n+1 X n T x ; wherein n=1-3, x=0-1, M includes at least one of Sc, Ti, Zr, Hf, V, Nb, Ta, Cr, and Mo, X includes at least one of carbon or nitrogen, and T includes at least one of -OH, -O, or -F.

[0013] The embodiment of the present invention also provides the use of the above-mentioned binder in a positive electrode plate.

[0014] The present embodiment also provides a positive electrode plate, comprising the above-mentioned binder.

[0015] The positive electrode plate provided in the embodiment of the present invention can effectively buffer the volume change of the positive electrode active material during the charge and discharge process, so that the battery has good interface contact throughout the entire charge and discharge cycle, and the smaller interface impedance can ensure good ion transmission performance of the electrode interface, thereby improving the cycle stability and rate performance of the battery.

[0016] The present invention also provides a method for preparing a positive electrode sheet, comprising the following steps:

[0017] (1) dispersing the polycarboxylate water-reducing agent and MXene in water and freeze-drying the mixture to obtain a mixed powder of the polycarboxylate water-reducing agent and MXene, and then dispersing the mixed powder in an organic solvent to obtain a binder colloid;

[0018] (2) Mixing the sulfide solid electrolyte, the positive electrode material and the binder colloid obtained in step (1), and then coating the mixture on the current collector and performing a heating treatment.

[0019] In some embodiments, in step (1), the organic solvent is a non-polar solvent or a weakly polar solvent, and the organic solvent includes any one of toluene, benzene, petroleum ether, and n-hexane;

[0020] And / or, the mass fraction of the binder in the binder colloid is 1 to 50%.

[0021] In some embodiments, in step (2), the mass ratio of the positive electrode material, the sulfide solid electrolyte and the binder is 80-99%, 0.5-10%, and 0.5-10%;

[0022] And / or, the temperature of the heating treatment is 130-170° C., and the time of the heating treatment is 10-15 hours;

[0023] The embodiments of the present invention also provide the use of the above-mentioned positive electrode sheet or the positive electrode sheet prepared by the above-mentioned preparation method in an all-solid-state battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The LiNi assembled in Example 1 and Comparative Example 1 0.8 Co 0.1 Mn 0.1 Long cycle performance diagram of O2 / Li all-solid-state battery at room temperature;

[0025] Figure 2 It is a long cycle performance diagram of the Sb2S3 / Na all-solid-state battery assembled in Example 2 and Comparative Example 2 at room temperature;

[0026] Figure 3 The Li assembled in Example 4 and Comparative Example 4 1.17 Mn 0.55 Ni 0.23 Co 0.05 Long cycle performance diagram of O2 / Li all-solid-state battery at room temperature;

[0027] Figure 4 The LiNi assembled in Example 5 and Comparative Example 5 0.8 Co 0.1 Mn 0.1 Long cycle performance diagram of O2 / Si all-solid-state battery at room temperature. DETAILED DESCRIPTION

[0028] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.

[0029] The binder according to the embodiment of the present invention includes a polycarboxylate water-reducing agent and MXene.

[0030] The binder of the embodiment of the present invention utilizes covalent bonding of a polycarboxylic acid water-reducing agent and a MXene material to prepare an integrated binder, thereby achieving uniform dispersion of the MXene material in a non-polar solvent, thereby serving as a solid-state battery binder; in the embodiment of the present invention, the sulfide solid electrolyte-based positive electrode prepared using the binder has low interfacial impedance, high interfacial stability, and high compatibility with high-voltage positive electrode active materials, which can significantly improve the electrochemical performance of the sulfide all-solid-state battery.

[0031] In some embodiments, preferably, the mass proportion of the polycarboxylate water-reducing agent is 10-40%, and the mass proportion of the MXene is 60-90%.

[0032] In the embodiment of the present invention, the mass ratio of carboxylic acid water-reducing agent and MXene is preferably selected, which not only ensures the uniform dispersion of MXene during the preparation process, but also reduces the interface impedance of sulfide solid electrolyte / positive electrode material; if the content of polycarboxylic acid water-reducing agent is too high, it may cause the electrolyte / positive electrode interface impedance to be too high; if the content of polycarboxylic acid water-reducing agent is too low, MXene cannot be uniformly dispersed.

[0033] In some embodiments, preferably, the structure of the polycarboxylate water-reducing agent is as shown in formula (1):

[0034]

[0035] In formula (1), R0 is selected from a carboxylic acid group or a sulfonic acid group; R1, R2, R3, R4, R5, and R6 are independently selected from hydrogen, halogen, carbamoyl, alkyl, alkoxy, alkylamino, alkylthio, alkoxysilyl, alkanoyl, sulfonyl, aryl, or heteroaryl; x is 0 to 1000, y is 100 to 1000, and z is 0 to 100.

[0036] In some embodiments, preferably, the chemical formula of the MXene is M n+1 X n T x; wherein n=1-3, x=0-1, M includes at least one of Sc, Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, X includes at least one of carbon or nitrogen, and T includes at least one of -OH, -O or -F.

[0037] The embodiment of the present invention also provides the use of the above-mentioned binder in a positive electrode sheet.

[0038] The present embodiment also provides a positive electrode plate, comprising the above-mentioned binder.

[0039] The positive electrode plate provided in the embodiment of the present invention can effectively buffer the volume change of the positive electrode active material during the charge and discharge process, so that the battery has good interface contact throughout the entire charge and discharge cycle, and the smaller interface impedance can ensure good ion transmission performance of the electrode interface, thereby improving the cycle stability and rate performance of the battery.

[0040] The present invention also provides a method for preparing a positive electrode sheet, comprising the following steps:

[0041] (1) dispersing the above-mentioned binder polycarboxylate water-reducing agent and MXene in water and then freeze-drying the mixture to obtain a mixed powder of the polycarboxylate water-reducing agent and MXene, and then dispersing the mixed powder in an organic solvent to obtain a binder colloid;

[0042] (2) Mixing the sulfide solid electrolyte, the positive electrode material and the binder colloid obtained in step (1), and then coating the mixture on the current collector and performing a heating treatment.

[0043] In some embodiments, preferably, in step (1), the organic solvent is a non-polar solvent or a weakly polar solvent, and the organic solvent includes any one of toluene, benzene, petroleum ether, and n-hexane.

[0044] In some embodiments, preferably, the mass fraction of the binder in the binder colloid is 1-50%, for example, 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, etc.

[0045] In some embodiments, preferably, in the step (2), the mass ratios of the positive electrode material, the sulfide solid electrolyte and the binder are: 80-99%, 0.5-10%, and 0.5-10%.

[0046] In the embodiment of the present invention, the mass ratio of the positive electrode material, the sulfide solid electrolyte and the binder is optimized to ensure good ion transmission performance at the electrode interface, which is beneficial to improving the cycle stability and rate performance of the battery.

[0047] In some embodiments, preferably, in step (2), the temperature of the heating treatment is 130-170°C, such as 130°C, 135°C, 140°C, 145°C, 150°C, 155°C, 160°C, 165°C, 170°C, etc., and the time of the heating treatment is 10-15h, such as 10h, 11h, 12h, 13h, 14h, 15h, etc.;

[0048] In some embodiments, preferably, in step (2), the sulfide solid electrolyte includes Li6PS5X, Li 10 D x P 3-x S 12 , Li2S: (1-x)P2S5, Li3PS4, Na3QS4, Na 10 D x P 3-x S 12 or at least one of Na2S:(1-x)P2S5, wherein X in the Li6PS5X comprises at least one of Cl, Br or I; 10 D x P 3-x S 12 wherein 0≤x≤2, D comprises at least one of Si, Ge or Sn; wherein x=0.7-0.8 in the Li2S:(1-x)P2S5; wherein Q comprises at least one of P or Sb; wherein Na 10 D x P 3-x In S1, 0≤x≤2, D includes at least one of Si, Ge or Sn; in the Na2S:(1-x)P2S5, x=0.7-0.8;

[0049] It is understood that for all-solid-state lithium batteries, the sulfide solid electrolyte includes Li6PS5X, Li 10 D x P 3- x S 12 , Li2S:(1-x)P2S5 or Li3PS4; for all-solid-state sodium batteries, the sulfide solid electrolyte includes Na3QS4, Na 10 D x P 3-x S 12 Or at least one of Na2S:(1-x)P2S5.

[0050] In some embodiments, preferably, the positive electrode material includes lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium cobalt manganese oxide, lithium rich manganese-based materials, nickel manganese spinel or Na xEG(CN)6, sodium vanadium phosphate, sulfur, sodium iron sulfate, elemental sulfur, elemental selenium, titanium disulfide, molybdenum disulfide, sodium ion fluorophosphate, sodium vanadium fluorophosphate, sodium iron fluorophosphate, sodium manganese oxide, sodium cobalt oxide, wherein the Na x In EG(CN)6, E and G are each independently selected from at least one of Fe, Co, Ni or Mn.

[0051] The embodiments of the present invention also provide the use of the above-mentioned positive electrode sheet or the positive electrode sheet prepared by the above-mentioned preparation method in an all-solid-state battery.

[0052] The technical solution of the present invention is described in detail below in conjunction with specific embodiments and drawings.

[0053] Example 1

[0054] (1) Polycarboxylate water reducer E1 and MXene material Ti3C2T x The mixture was uniformly dispersed in water at a mass ratio of 2:5, and a 20 wt% aqueous solution was prepared and freeze-dried for 12 hours to obtain a MXene / E1 mixed powder, which was then dissolved in toluene to prepare an A1 binder colloid with a mass fraction of 20%;

[0055] (2) The positive electrode material (LiNi 0.8 Co 0.1 Mn 0.1 O2), sulfide solid electrolyte particles (Li8GeS6), and A1 binder colloid were stirred and mixed in a glove box in the ratio of 88wt%, 10wt% and 2wt% for 12 hours, the evenly stirred slurry was evenly coated on an aluminum foil with a scraper, and dried at 150°C for 12 hours to obtain a sulfide solid electrolyte composite positive electrode.

[0056] The structural formula of polycarboxylate water reducer E1 is:

[0057] Among them, x=1000, y=100, z=50, m=10.

[0058] The loading of the positive electrode material in the composite positive electrode based on the polycarboxylate water-reducing agent / MXene integrated binder obtained in this example is 10 mg / cm 2 The ionic conductivity at room temperature is 0.8 mS cm -1 .

[0059] Example 2

[0060] (1) Polycarboxylate water reducer E2 and MXene material Ti2CT xThe mixture was uniformly dispersed in water at a mass ratio of 1:5, and a 20 wt% aqueous solution was prepared and freeze-dried for 12 hours to obtain a MXene / E2 mixed powder, which was then dissolved in toluene to prepare an A2 binder colloid with a mass fraction of 10%;

[0061] (2) In a dry atmosphere, the positive electrode material (Sb2S3), sulfide solid electrolyte particles (Na3PS4), and A2 binder colloid were stirred and mixed in a glove box at a ratio of 87wt%, 8wt% and 5wt% for 12 hours. The stirred slurry was evenly coated on an aluminum foil with a spatula and dried at 150°C for 12 hours to obtain a sulfide solid electrolyte composite positive electrode.

[0062] The structural formula of polycarboxylate water reducer E2 is:

[0063] Among them, x=2000, y=200, z=100, m=10.

[0064] The loading of the positive electrode material in the composite positive electrode based on the polycarboxylate water-reducing agent / MXene integrated binder obtained in this example is 8 mg / cm 2 The ionic conductivity at room temperature is 0.5 mS cm -1 .

[0065] Example 3

[0066] (1) Polycarboxylate water reducer E3 and MXene material Ti3C2T x The MXene / E3 mixed powder was obtained by uniformly dispersing them in water at a mass ratio of 3:7, preparing a 20 wt% aqueous solution and freeze-drying it for 12 hours. The mixed powder was dissolved in toluene to prepare an A3 binder colloid with a mass fraction of 15%.

[0067] (2) In a dry atmosphere, the positive electrode material (LiNi 0.6 Co 0.2 Mn 0.2 O2), sulfide solid electrolyte particles (Li7SnS 5.5 ), A3 binder colloid was stirred and mixed in a glove box in a ratio of 87wt%, 10wt% and 3wt% for 12 hours. The stirred slurry was evenly coated on an aluminum foil with a scraper and dried at 150°C for 12 hours to obtain a sulfide solid electrolyte composite positive electrode.

[0068] The structural formula of polycarboxylate water reducer E3 is:

[0069] x=1000, y=400, z=200, m=20.

[0070] The positive electrode material loading in the composite positive electrode based on polycarboxylate water-reducing agent / MXene integrated binder obtained in this example is 20 mg / cm 2 The ionic conductivity at room temperature is 1 mS cm -1 .

[0071] Example 4

[0072] (1) Polycarboxylate water reducer E4 and MXene material Ti3C2F x The MXene / E4 mixed powder was uniformly dispersed in water at a mass ratio of 1:9, and a 20 wt% aqueous solution was prepared and freeze-dried for 12 hours to obtain the MXene / E4 mixed powder, and the mixed powder was dissolved in n-hexane to prepare an A4 binder colloid with a mass fraction of 5%;

[0073] (2) In a dry atmosphere, the positive electrode material (Li 1.17 Mn 0.55 Ni 0.23 Co 0.05 O2), sulfide solid electrolyte particles (Li7SnS 5.5 ), A4 binder colloid was stirred and mixed in a glove box at a ratio of 89wt%, 8wt% and 3wt% for 12 hours. The stirred slurry was evenly coated on aluminum foil with a scraper and dried at 150°C for 12 hours to obtain a sulfide solid electrolyte composite positive electrode.

[0074] The structural formula of polycarboxylate water reducer E4 is:

[0075] x=500, y=300, z=100, m=10.

[0076] The positive electrode material loading in the composite positive electrode based on polycarboxylate water reducer / MXene integrated binder obtained in this example is 6 mg / cm 2 The ionic conductivity at room temperature is 1.1 mS cm -1 .

[0077] Example 5

[0078] (1) The same as step (1) of Example 3;

[0079] (2) In a dry atmosphere, the positive electrode material (LiNi 0.8 Co 0.1 Mn 0.1 O2), sulfide solid electrolyte particles (Li7P3S 11 ), A3 binder colloid was stirred and mixed in a glove box in a ratio of 89wt%, 9wt% and 2wt% for 12 hours. The stirred slurry was evenly coated on an aluminum foil with a scraper and dried at 150°C for 12 hours to obtain a sulfide solid electrolyte composite positive electrode.

[0080] The positive electrode material loading in the composite positive electrode based on polycarboxylate water-reducing agent / MXene integrated binder obtained in this example is 20 mg / cm 2 The ionic conductivity at room temperature is 1.2 mS cm -1 .

[0081] Example 6

[0082] (1) is the same as step (1) of Example 4;

[0083] (2) In a dry atmosphere, the positive electrode material (LiCoO2) sulfide solid electrolyte particles (Li 9.54 Si 1.74 P 1.44 S 11.7 Cl 0.3 ), A4 binder colloid was stirred and mixed in a glove box at a ratio of 87wt%, 10wt% and 3wt% for 12 hours. The stirred slurry was evenly coated on aluminum foil with a scraper and dried at 150°C for 12 hours to obtain a sulfide solid electrolyte composite positive electrode.

[0084] The positive electrode material loading in the composite positive electrode based on polycarboxylate water-reducing agent / MXene integrated binder obtained in this example is 25 mg / cm 2 The ionic conductivity at room temperature is 1.2 mS cm -1 .

[0085] Comparative Example 1

[0086] The method of this comparative example is the same as that of Example 1, except that step (1) is eliminated and PTFE is used as a binder in step (2) to prepare a composite positive electrode.

[0087] Comparative Example 2

[0088] The method of this comparative example is the same as that of Example 2, except that step (1) is eliminated and PTFE is used as a binder in step (2) to prepare a composite positive electrode.

[0089] Comparative Example 3

[0090] The method of this comparative example is the same as that of Example 3, except that step (1) is eliminated and PTFE is used as a binder in step (2) to prepare a composite positive electrode.

[0091] Comparative Example 4

[0092] The method of this comparative example is the same as that of Example 4, except that step (1) is eliminated and PTFE is used as a binder in step (2) to prepare a composite positive electrode.

[0093] Comparative Example 5

[0094] The method of this comparative example is the same as that of Example 5, except that step (1) is eliminated and PTFE is used as a binder in step (2) to prepare a composite positive electrode.

[0095] Comparative Example 6

[0096] The method of this comparative example is the same as that of Example 6, except that step (1) is eliminated and PTFE is used as a binder in step (2) to prepare a composite positive electrode.

[0097] The performance of the composite positive electrodes prepared in Examples 1 to 6 and Comparative Examples 1 to 6 was tested.

[0098] (1) According to 0.1C rate, 2.7-4.5V (vs.Li + / Li) voltage range, the composite positive electrode prepared in Example 1 and Comparative Example 1 was charged and discharged. The results are as follows Figure 1 As shown, from Figure 1 It can be seen that the composite cathode LiNi based on polycarboxylate water reducer / MXene integrated binder 0.8 Co 0.1 Mn 0.1 The capacity retention rate of the O2 / Li all-solid-state battery after 50 cycles is 98%, while that of the composite positive electrode / Li all-solid-state battery with PTFE as a binder is only 65%.

[0099] (2) According to 0.1C rate, 0.1-2.5V (vs.Na + The composite positive electrodes prepared in Example 2 and Comparative Example 2 were subjected to charge and discharge tests within a voltage range of 1000V / Na. The results are shown in FIG. Figure 2 As shown, the capacity retention rate of the composite positive electrode Sb2S3 / Na all-solid-state battery using a polycarboxylate superplasticizer / MXene integrated binder after 50 cycles is 98%, while the retention rate of the composite positive electrode Sb2S3 / Na all-solid-state battery using PTFE as a binder is only 94%.

[0100] (3) According to 0.1C rate, 2.7-4.5V (vs.Li + The composite positive electrode prepared in Example 3 and Comparative Example 3 was charged and discharged within a voltage range of 100 V. The composite positive electrode LiNi based on the polycarboxylate water reducer / MXene integrated binder was used. 0.6 Co 0.2 Mn 0.2 The capacity retention rate of the O2 / Li all-solid-state battery after 200 cycles is 90%, while that of the composite positive electrode / Li all-solid-state battery with PTFE as binder is only 50%.

[0101] (4) According to 0.2C rate, 2.7-4.9V (vs.Li + / Li) voltage range, the composite positive electrode prepared in Example 4 and Comparative Example 4 was subjected to charge and discharge tests. Figure 3 As shown, the composite cathode Li using polycarboxylate water reducer / MXene integrated binder 1.17 Mn 0.55 Ni 0.23 Co 0.05 The capacity retention rate of the O2 / Li all-solid-state battery after 150 cycles is 95%, while that of the composite positive electrode / Li all-solid-state battery with PTFE as a binder is only 75%.

[0102] (5) According to 0.1C rate, 2.7-4.5V (vs.Li + / Li) voltage range, the composite positive electrode prepared in Example 5 and Comparative Example 5 was charged and discharged. The results are as follows Figure 4 As shown, the composite cathode LiNi using polycarboxylate water reducer / MXene integrated binder 0.8 Co 0.1 Mn 0.1 The capacity retention rate of the O2 / Si all-solid-state battery after 50 cycles is 99%, while that of the composite positive electrode / Li all-solid-state battery with PTFE as a binder is only 78%.

[0103] (6) According to 0.5C rate, 2.7-4.4V (vs.Li + / Li) voltage range, the composite positive electrodes prepared in Example 6 and Comparative Example 6 were subjected to charge and discharge tests. The capacity retention rate of the composite positive electrode LiCoO2 / Li all-solid-state battery using polycarboxylic acid water-reducing agent / MXene integrated binder after 300 cycles was 88%, while the capacity retention rate of the composite positive electrode / Li all-solid-state battery using PTFE as a binder was only 60%.

[0104] The mechanism for improving the battery cycle performance in the embodiment of the present invention is that the polycarboxylate water-reducing agent / MXene integrated binder can enable the battery to have good interface contact throughout the entire charge and discharge cycle, and the smaller interface impedance can ensure good ion transmission performance at the electrode interface, thereby improving the cycle stability of the battery.

[0105] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0106] Although the above embodiments have been shown and described, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. Changes, modifications, substitutions and variations of the above embodiments by those of ordinary skill in the art are all within the scope of protection of the present invention.

Claims

1. A binder, characterized in that: Including polycarboxylate water reducer and MXene.

2. The adhesive according to claim 1, characterized in that The mass proportion of the polycarboxylate water-reducing agent is 10-40%, and the mass proportion of the MXene is 60-90%.

3. The adhesive according to claim 1 or 2, characterized in that: The structure of the polycarboxylate water reducer is shown in formula (1): In formula (1), R0 is selected from a carboxylic acid group or a sulfonic acid group; R1, R2, R3, R4, R5, and R6 are independently selected from hydrogen, halogen, carbamoyl, alkyl, alkoxy, alkylamino, alkylthio, alkoxysilyl, alkanoyl, sulfonyl, aryl, or heteroaryl; x is 0 to 1000, y is 100 to 1000, and z is 0 to 100.

4. The adhesive according to claim 1 or 2, characterized in that: The chemical formula of the MXene is M n+1 X n T x ; wherein n=1-3, x=0-1, M includes at least one of Sc, Ti, Zr, Hf, V, Nb, Ta, Cr, Mo, X includes at least one of carbon or nitrogen, and T includes at least one of -OH, -O or -F.

5. Use of the binder according to any one of claims 1 to 4 in a positive electrode sheet.

6. A positive electrode sheet, characterized in that: The invention comprises the adhesive according to any one of claims 1 to 4.

7. The method for preparing a positive electrode sheet according to claim 6, characterized in that: The following steps are involved: (1) dispersing the polycarboxylate water-reducing agent according to any one of claims 1 to 4 and MXene in water and then freeze-drying the mixture to obtain a mixed powder of the polycarboxylate water-reducing agent and MXene, and then dispersing the mixed powder in an organic solvent to obtain a binder colloid; (2) Mixing the sulfide solid electrolyte, the positive electrode material and the binder colloid obtained in step (1), and then coating the mixture on the current collector and performing a heating treatment.

8. The method for preparing a positive electrode sheet according to claim 7, characterized in that: In the step (1), the organic solvent is a non-polar solvent or a weakly polar solvent, and the organic solvent includes any one of toluene, benzene, petroleum ether, and n-hexane; And / or, the mass fraction of the binder in the binder colloid is 1 to 50%.

9. The method for preparing a positive electrode sheet according to claim 7, characterized in that: In the step (2), the mass ratio of the positive electrode material, the sulfide solid electrolyte and the binder is 80-99%, 0.5-10% and 0.5-10%; And / or, the temperature of the heating treatment is 130-170° C., and the time of the heating treatment is 10-15 hours.

10. Use of the positive electrode sheet according to claim 6 or the positive electrode sheet prepared by the preparation method according to any one of claims 7 to 9 in an all-solid-state battery.

Citation Information

Patent Citations

  • Titanium suboxide / MXene / Co3O4 composite electrode and preparation method thereof

    CN113292139A

  • Preparation method of point-line-plane three-in-one high-stability three-dimensional network structure electrode

    CN115602850A

  • Polycarboxylic acid aqueous binder containing coupling amide bond and its preparation method and application in lithium ion battery

    CN108832126A

  • MXenes modified conductive adhesive and preparation method thereof

    CN114181653A

  • Reduction type MXene polycarboxylate superplasticizer and preparation method thereof

    CN118165282A